Determination of thermodynamic properties of poly[2-(3-methyl-3-phenylcyclobutyl)-2-hydroxyethylmethacrylate] and its copolymers at infinite dilution using inverse gas chromatography - Kaya, I; Demirelli, K (Elsevier Sci Ltd, 2000)
Some thermodynamic quantities were obtained for the interactions of poly[2-(3-phenylcyclobutyl)-2-hydroxyethylmethacrylate], (PPCHEMA) poly[2-(3-phenylcyclobutyl)-2-hydroxyethylmethacrylate-acrylonitrile] (PPCHEMA-AN) and poly[2-(3-methyl-3-phenylcyciobutyl)-2-hydroxyethylmethacrylate-styrene] (PPCHEMA-S) with alcohols, ketones, acetates, aromatics and alkanes by inverse gas chromatography method in various temperatures. The specific retention volumes, V-g(0), weight fraction activity coefficients of solute probes at infinite dilution, Omega(1)(infinity), Flory-Huggins thermodynamic interaction parameters, chi(12)(infinity), between polymers and solvents are determined. The partial molar free energy, Delta G(1)(infinity), the partial molar heat of mixing, Delta H-1(infinity), at infinite dilution and the solubility parameters of polymer, delta(2), were calculated at various temperatures. The glass transition temperatures, T-g, of PPCHEMA, PPCHEMA-AN and PPCHEMA-S were found to be about 378, 377 and 375 K, respectively, by differential scanning calorimetry. Alcohols, ketones and acetates were found to be good solvent for PPCHEMA and PPCHEMA-AN but n-alkanes and aromatics (except for high temperatures) were found to be non-solvents. Whereas for PPCHEMA-S all solvents were found to be non-solvents at this temperatures. Also the solubility parameters for PPCHEMA, PPCHEMA-AN and PPCHEMA-S at infinite dilution were found by plotting the graph of [(delta(1)(2)/RT) - chi(12)(infinity)/V-1] versus solubility parameters, delta(1), of this probes. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: poly2-(3-methyl-3-phenylcyclobutyl)-2-hydroxyethyl methacrylate and its copolymers; inverse gas chromatography; polymer-solvent interactions